Appraising the Determinants and Outcomes of Islamic Financial Literacy through the Lens of a Systematic Literature Review - Abdul Aziz, Muhammad Ridzuan; Saad, Abidah; Jamaludin, Salwaty; Nik Hashim, Nik Mohd Hazrul; Samat, Nusrah; Muhamad Nor, Nor Shahrul Nizam (Information Management and Business Review, 2024)
This research illuminates the determinants and outcomes of Islamic financial literacy as scrutinized in prior investigations. A systematic literature review unfolded across the Scopus database from 2016 to 2023. This investigation encompasses 22 articles from the 40 scholarly works extracted from the Scopus database. The Journal of Islamic Accounting and Business Research emerges as the most prolific disseminator of insights into the determinants and outcomes of Islamic financial literacy, credited to its robust publication frequency throughout the year. The autonomous and reliant facets of Islamic financial literacy were predominantly studied, with emphasis not only on individual dynamics but also on business perspectives. The determinants instigating Islamic financial literacy congregate within the affective, conative, family influence, self-controlled, and demographic predictors. Conversely, the ramifications stemming from Islamic financial literacy manifest in cognitive, affective, and conative dimensions, leaving an indelible imprint on the business realm. Geographic focus reveals a concentration of prior investigation within Muslim-majority nations, predominantly Indonesia. Furthermore, the investigation discovers that past studies were mainly conducted in the context of Islamic banking. The evidence from the present study provides input to researchers in conducting further research on Islamic financial literacy.